Mathematical Communication Profiles on Learning Styles in Solving High School Level Mathematics Problems - Andriani, Wiwik; Nurmayaningsih, Nurmayaningsih (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This study aims to see the mathematics communication of students in terms of learning styles in solving high school mathematics problems. The focus of this research is: students' mathematics communication in terms of visual learning styles, mathematics communication in terms of auditory learning styles, mathematics communication in terms of kinesthetic learning styles. The subjects of this study were students at SMA Negeri 1 Gowa who were grouped based on their learning styles. The research instrument is the researcher himself, because the researcher himself plans what to ask the research subjects. Data collection techniques are carried out by providing learning style questionnaires, carrying out written tests to see mathematical communication skills, and interview guidelines. This study used technical triangulation with data analysis techniques, namely data presentation, data reduction, and conclusions. The results of this study indicate that the level of mathematics communication can be seen from the learning styles of students. Students with visual and auditory learning styles are able to solve mathematical problems completely and in detail, are able to use mathematical ideas, are able to use mathematical notations and symbols to determine answer conclusions. Students who have a kinesthetic learning style are also able to solve mathematical problems in their own style and way, namely a shorter way, being able to use mathematical ideas, symbols and mathematical notations in solving problems, but they do not provide conclusions from the answers that are done